Influence of sol counter-ions on the anatase-to-rutile phase transformation and microstructure of nanocrystalline TiO2 - Tobaldi, D. M.
Amongst nanomaterials, metal oxides play an increasingly dominant role, with titanium dioxide (titania, TiO2) being widely used for various applications, such as light-to-energy conversion and storage, and photocatalysis. In this work, TiO2 has been synthesised via an aqueous sol-gel method, using three different mineral acids (HNO3, HCl and HBr) to peptise the sol, and hence provide counter-ions. Dried sols were thermally treated at three different temperatures (450, 600 and 800 degrees C),using three different dwell times (2, 4, and 8 h). Advanced X-ray methods were used to monitor the effect that the counter-ions had on the anatase-to-rutile phase transformation (ART). Quantitative phase analysis (QPA) using the Rietveld method was applied to assess the true amount of crystalline phases in the systems, and the amount of amorphous phase. Furthermore, the average crystalline domain diameter was also investigated, using whole powder pattern modelling (WPPM). With the advanced XRPD data (actual crystalline phase weight fraction in the samples and their average domain diameter and size distribution), it was possible to carry out a semi-quantitative study of the ART transformation kinetics. At a low temperature of 75 degrees C, the Cl-counter-ion was the most favourable to obtain anatase as the major crystalline phase, delaying the onset of the ART. Conversely, the Br-ions, maintained more anatase at 450 degrees C, with a lower ART rate. In general, halides were more effective in delaying the ART than NO3- counterions. Moreover, we observed an inverse linear relationship between the lattice volume expansion of rutile and the increase of its crystalline domain size at 450 and 600 degrees C isotherms. As the domain sizes increased with temperature, this effect reversed and became a direct linear dependence at the 800 degrees C isotherm, suggesting a critical size limit < 90 nm for this effect.